Some results on the main supergraph of finite groups - Asboei, A.K.; Salehi, S.S. (Algebra and Discrete Mathematics, 2020)
Let G be a finite group. The main supergraph S(G) is a graph with vertex set G in which two vertices x and y are adjacent if and only if o(x) | o(y) or o(y) | o(x). In this paper, we will show that G ≅ PSL(2, p) or PGL(2, p) if and only if S(G) ≅ S(PSL(2, p)) or S( PGL(2, p)), respectively. Also, we will show that if M is a sporadic simple group, then G ≅ M if only if S(G) ≅ S(M).